2022
DOI: 10.4049/jimmunol.208.supp.115.23
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between the Environment and Genetics determines immune variation in rewilded mice

Abstract: Immune responses to pathogens and vaccination can be varied with some individuals inducing optimal responses while others do not. The host genetic profile, environment and previous microbial experience could influence an individual’s response, but the relative contribution, and interactions of these different factors remains largely unknown. Here, using various multi-omics, ecological and single cell approaches, we show that release of genetic inbred strains of mice, 129-SL, PWK and C57/B6 mice, to a rewilded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The fact that social association predicts adaptive immune similarity in the MLNs but not the blood may reflect the role of the lymph nodes as sites of that antigen recognition. In our analysis of GxE effects on immune phenotype (25) we found that environment had more effect on immune cell composition in the blood than in the MLNs. However, here we are investigating within-strain heterogeneity in a single shared environment, so we may have a different predictor for something that would have been noise…”
Section: C)mentioning
confidence: 77%
See 2 more Smart Citations
“…The fact that social association predicts adaptive immune similarity in the MLNs but not the blood may reflect the role of the lymph nodes as sites of that antigen recognition. In our analysis of GxE effects on immune phenotype (25) we found that environment had more effect on immune cell composition in the blood than in the MLNs. However, here we are investigating within-strain heterogeneity in a single shared environment, so we may have a different predictor for something that would have been noise…”
Section: C)mentioning
confidence: 77%
“…We collected blood samples for Complete Blood Count (CBC) analysis prior to release and two weeks post-release, when we challenged a subset of mice with Trichuris muris, an intestinal nematode parasite. At five weeks post-release, prior to any shedding of T. muris eggs, we trapped out the mice for extensive immune phenotyping (25) and collected fecal samples for 16S microbiome analysis. We analyzed our data using Bayesian linear regression models with appropriate response variable distributions and priors to generate posterior probability distributions for the associations between predictors and response variables (see Methods).…”
mentioning
confidence: 99%
See 1 more Smart Citation